Mechanisms of alkali pH-shifted colour changes in squid (Uroteuthis edulis) subjected to frozen storage. (16th April 2023) - Xu, Zheng; Chen, Yunyun; Zhou, Xuxia; Liu, Shulai; Xie, Jing; Dai, Wangli; Zhu, Shichen; Ding, Yuting
Graphical abstract: Highlights: Strong alkali treatment effectively improves the redness of squid skin; Strong alkali treatment disrupts the structure and morphology of pigment granules; The red pigment dissolves well in strong alkaline aqueous solution; Water-soluble yellow pigment in squid skin is destroyed by strong alkali treatment. Abstract: The skin discoloration of squid subjected to frozen storage negatively affects market price. In this study, various alkali treatments were investigated for effects on red granules and yellow pigments of squid skin and corresponding mechanisms were investigated at the tissue, cellular and molecular level. A significant colour improvement was observed when subjected to a pH 12 treatment, supported by decreased Δ b * and increased Δ a * values. Neither lower nor harsher alkali treatments than pH 12 can not obtain such results. HE staining and the UV–vis spectrum suggest that the improved red colour in skin was ascribed to the release of red pigment granules from damaged chromatophores by alkaline treatment and the release of red pigments in alkaline aqueous solutions from granules. However, based on TEM and particle size analysis, an excessive alkali treatment of pH 13 would degrade granules into smaller particles. The degradation of yellowness pigments indicated high sensitivity to alkali environments according to HPLC results. This study provides a valuable reference for improving the colour appearance of squid skin subjected to frozen storage.